TANGGUNG JAWAB PENGANGKUT TERHADAP PENUMPANG YANG TIDAK TERDAFTAR DALAM MANIFES (STUDI KASUS JATUHNYA PESAWAT LION AIR JT 610 DI KARAWANG) - Abimanyu Faiz Prajogo; H. K. Martono (Jurnal Hukum Adigama, 2019)
Lion Air with fligh code JT-610 route Jakarta to Pangkal Pinang on October 29th, 2028 which crashed in Karawang Waters carrying 178 passengers, one child passenger, 2 babies, and 7 cabin crew. On the plane there are passengers who are not on the ticket or not registered. Issues issued are how the responsibility of the carrier in an aircraft accident that is not listed in the passenger manifest. The research method used in this thesis research is normative legal research. The results of the research prove that passengers who are not in the manifest may receive compensation, but only compensate for voluntary purchases. It may be possible to request ex gratia or voluntarily to buy a passenger ticket that cannot be ordered in the passenger manifest. However, based on information compiled from PT Jasa Raharja, checking the heirs or families of victims of the crash of the Lion Air JT 610 aircraft which were not equipped in the manifest of the aircraft could still receive compensation. In cases that substitute for consumer rights, caution is needed in analyzing who should be held responsible and asking for the responsibilities required for the parties concerned.